The collaboration of green design & technology towards business sustainability in Malaysian manufacturing industry - Md Taib, Mohd Yazid; Mohamed Udin, Zulkifli; Abdul Ghani, Abdullah (Elsevier, 2015)
At present, global businesses are operating in a hyper competitive scenario in which supremacy is incontestably a fulcrum in sustainability.In achieving this, businesses require a systematic and comprehensive management in a superior way to overcome the huge competitive circumstances faced by globalizes milieu.Logically, by implementing the green management which intertwined, co-formulated and co-implemented with the technology are enabling the businesses particularly in manufacturing to retain the sustainability status quo and outperformed the rivals.Specifically, in Malaysia's manufacturing accentuates the necessity of fulfillment the drivers of green management and technology in sustaining business.Accordingly, at the end the implications of these conceptual collaborations are presented for practitioners and researchers.